The Strategic Role of "Rumah Data" As an Institutional Innovation in Election Supervision at the Regency Level - Amin, Muhammad Masykur (Indonesian Journal of Political Studies, 2025)
Elections are a key feature of democratic states, serving as a legal mechanism to fill political positions based on the people's choices. In practice, the credibility of election management bodies largely depends on accurate and transparent data management. This study explores the use of the Rumah Data (Data Center), an initiative by the East Java Provincial Bawaslu, as a tool to support election oversight, with a focus on Bawaslu of Bojonegoro Regency. The research addresses a gap in existing studies, which have mostly examined the Siwaslu application developed by the national Bawaslu, whereas Rumah Data represents a regional innovation. This study employs a descriptive qualitative method, with data collected through interviews, documentation, and literature review. The findings reveal that Rumah Data plays a strategic role in enhancing transparency, accountability, and the effectiveness of election monitoring. The study recommends strengthening human resources and digital system development to optimize Rumah Data in the future.